Interceptive orthodontic treatment in Singapore: A descriptive study - Yi Lin Song; Elaine Li Yen Tan; Benn Chi Jin Chua; Rachel Jing Yi Ng; Natalie Kar Poh Lam (Proceedings of Singapore Healthcare, 2020)
Background: The benefits of interceptive orthodontic treatment have always been a subject of much debate, and it is understandable that clinicians are confused about how to advise parents of potential interceptive orthodontic patients. Objective: The aim is to study the treatment outcomes of interceptive orthodontics associated with different appliances. Demographic information on patients presenting for interceptive treatment, prevalence and types of dental conditions treated, types and frequency of appliances used, treatment duration and the number of visits taken were also investigated. Methods: This study involved analyzing records of interceptive orthodontic patients seen at the National Dental Centre Singapore from January 2011 to December 2017. Treatment outcomes were divided into success, improvement and failure according to pre-determined treatment objective parameters. Results: A total of 1324 patient records (654 females, 670 males) were studied, with an average age of 10.6±1.9 years. The most common dental condition seen was the anterior crossbite while the most common interceptive orthodontic appliance used was the bite plate. Average treatment duration was 10.8±6.8 months (9.8±9.2 visits) for fixed appliances, 7.5±6.5 months (6.9±3.4 visits) for removable appliances and 10.8±3.2 months (12.6±3.3 visits) for a combination. Interceptive orthodontic treatment had an overall success rate of 75.5%, improvement rate of 9.5% and failure rate of 15.0%. The most common reason for failure was attributed to non-compliance. Conclusion: The data above shed light on interceptive orthodontic treatment in an Asian population and gives useful information for primary care clinicians to provide for concerned parents.